The Influence of Belief, Utility of Information, and Group Support on Selective Exposure to Pornography Among Teenagers in Jakarta, Indonesia - Hutagalung, Inge (International Journal of Engineering and Technology, 2018)
Festinger’s (1) hypothesis cites belief as a variable that influences selective exposure. However, a review of other experts’ research proves that selective exposure is not only affected by the psychological aspect but by the message and the social aspect as well. In contrast to previous scholars who focused only on one variable, the researcher examines belief, utility of information, and group support simultaneously and integrates them into a model. The research design is a case study involving the use of pornographic information. This study’s subjects comprise 400 senior high school students in Jakarta, Indonesia. The relationships among the variables were tested by using structural equation modeling. The validity and reliability analyses utilized the LISREL 8.80 application. A questionnaire with a Likert-scale model was used as the data collection method. The structural test results show that the theoretical models for the three variables have a significant effect on selective exposure (t value ≥ 1.96). On the other hand, the findings also prove that communication in the context of selective information on pornography is divided into three levels. First, at the intrapersonal level, the individual holds on to his or her belief in selecting the information. Second, at the interpersonal or group level, the individual adjusts his or her belief to the existing reality (environment or social group). Third, at the mass communication level, the individual selects the information according to its utility, that is, to fulfill the need for information.
Keywords: belief; utility of information; group support